Urethral Caruncle Presented as Premature Menarche in a 4-Year-Old Girl - Manori Gamage; D. Beneragama (Case Reports in Pediatrics)
Urethral caruncle (UC) is a benign fleshy outgrowth at the urethral meatus. It was first described by Samuel Sharp in 1750 and occurs mainly at the posterior lip of the urethra, and the exact aetiology is still uncertain. More often it was seen in the postmenopausal women, and only few cases are reported in young girls. Patients may be asymptomatic and could find this as an incidental finding or they may present with symptoms such as dysuria, bleeding per vagina, haematuria, a mass protruding through vagina, and acute retention of urine. Here, we report the case history of a 4-year-old girl presented with vaginal bleeding which was taken as she has attended menarche and found to have urethral caruncle which was the cause for bleeding. Histology confirmed the diagnosis, and girl was completely cured following surgical excision.